Students' Interest in Learning Mathematics Using Augmented Reality: Rasch Model Analysis - Ilham Muhammad; Lilis Marina Angraini; Rani Darmayanti; Rahmad Sugianto; Usmiyatun Usmiyatun; Paulo Vitor da Silva Santiago (CV. Edutechnium Indonesia, 2023)
Interest in learning is a source of intrinsic motivation that encourages students to do what they want so that it has an impact on student achievement. The purpose of this study is to obtain information about the interests in learning mathematics for MTs students while learning using Augmented Reality media. Quantitative descriptive method is used in this research. Respondents in this study amounted to 20 students at MTs. Data was collected from a student interest questionnaire with 18 statement items which were analyzed using the Rasch model. The results showed that the quality of the statements in the questionnaire was included in the sufficient category, and the level of consistency of students' answers was also in the sufficient category. Cronbach's alpha value is in the very good category, namely 0.85 which can be used to assess the reliability of the interaction between Person and the item as a whole. Furthermore, the level of student interest in MTs in Kampar using Augmented Reality learning media is in the high category. The logit value is 1.62, meaning that the statement items are mostly approved by students